2018
DOI: 10.1007/s10533-018-0496-0
|View full text |Cite
|
Sign up to set email alerts
|

Soil respiration partitioning in afforested temperate peatlands

Abstract: Understanding and quantifying soil respiration and its component fluxes are necessary to model global carbon cycling in a changing climate as small changes in soil CO2 fluxes could have important implications for future climatic conditions. A soil respiration partitioning study was conducted in eight afforested peatland sites in southwest Ireland. Using trenched points, annual soil CO2 emissions, and the contributions of autotrophic and heterotrophic respiration as components of total soil respiration, were es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 56 publications
0
21
0
Order By: Relevance
“…A similar effect of the temperature, rainfall and WTD conditions on soil CO 2 emissions was found by Wilson et al (2016) when developing C EF for peatlands managed for peat extraction in the same climatic zone. In addition, Jovani‐Sancho et al (2018) showed that R H fluxes increased with deeper WTD (greater aerobic conditions in the peat) and that this CO 2 efflux was maximum when WTD was −66 cm. This would support the present results.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A similar effect of the temperature, rainfall and WTD conditions on soil CO 2 emissions was found by Wilson et al (2016) when developing C EF for peatlands managed for peat extraction in the same climatic zone. In addition, Jovani‐Sancho et al (2018) showed that R H fluxes increased with deeper WTD (greater aerobic conditions in the peat) and that this CO 2 efflux was maximum when WTD was −66 cm. This would support the present results.…”
Section: Discussionmentioning
confidence: 99%
“…While continuous soil T was averaged for hourly and daily values, WTD gaps between consecutive measurements were filled by linear interpolation. For a full description of the soil respiration chamber and the measurements method see Jovani‐Sancho et al (2018).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations